STRATEGI HILIRISASI DAN ANALISIS NILAI TAMBAH GULA AREN SEMUT MELALUI PENGUATAN KELEMBAGAAN PETANI DI DESA PENANTIAN KABUPATEN OKU SELATAN - Anggi Fatmayati, Andri Irawan, Neng Karmila (JASEP, 2026)
This study aims to formulate a strategy for strengthening palm sugar farmers' institutions and analyze product value added in Penantian Village, Banding Agung District, South OKU Regency. The method used in this research is a combination of quantitative and qualitative methods through the added value analysis approach (Hayami Method) and strategic analysis (Rangkuti's SWOT Matrix). Data collection was conducted through observation and in-depth interviews with 45 palm sugar farmers. The results showed that processing palm sap into ants sugar (granulated palm sugar) produced a value added ratio of 57%, significantly higher than molded palm sugar which only reached 28%. Based on the SWOT matrix, the institutional position of farmers is in Quadrant I (Aggressive), indicating strong internal strengths and significant external opportunities for business development. The institutional strengthening strategy is focused on forming collective business units to facilitate technological modernization, quality standardization (P-IRT and Halal certification), and integrated marketing with the tourism potential of Ranau Lake. Strengthening these institutions is expected to increase farmers' bargaining power and optimize the downstreaming of palm sugar products sustainably.